Концептуальний соціально-економічний та технічний сценарій формування інноваційної політики України - Онікієнко, В.В.; Ємельяненко, Л.М. (Інститут демографії та соціальних досліджень НАН України, 2007)
В статье обоснована реальная необходимость активизации инновационной деятельности государства на этапе становления экономики знаний в глобальном масштабе. Предложен концептуальный сценарий разработки государственной политики на основе формирования требований к национальной инновационной концепции, принципов и приоритетов реализации стратегии инновационного развития Украины. In the article the real necessity of the state innovative activity activation on the stage of becoming of economy of knowledge on a global scale is grounded. The conceptual scenario of state policy development on the basis of forming of requirements to national innovative conception, principles and priorities of realization of innovative development strategy of Ukraine is offered.